PELESTARIAN BUDAYA LAMPUNG DI ERA GLOBALISASI: ANTARA TRADISI DAN MODERNITAS - Sagita, Hardi; Achyari, Asrul; Prayogi, Rahmat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This research aims to describe and analyze the preservation strategies of Lampung Culture amidst the challenges of globalization and modernity. Lampung Culture, rooted in the life philosophy of Piil Pesenggiri (which embodies Juluk Adek (self-esteem and traditional title), Nemui Nyimah (hospitality), Nengah Nyappur (sociability and equality), and Sakai Sambayan (mutual cooperation)), is facing the threat of value erosion due to the domination of global popular culture. Globalization, defined as the intensification of worldwide social relations, brings about value homogenization that potentially displaces authentic local traditions. This study employs a descriptive qualitative approach, with research locations in Tulang Bawang, Central Lampung, and South Lampung Regencies, representing the Saibatin and Pepadun indigenous communities. Data were collected through in-depth interviews, participant observation (such as in the Begawi and Cangget Agung ceremonies), and documentation. Data analysis utilized the Miles and Huberman model (data reduction, data display, and conclusion drawing). The results indicate that the preservation of Lampung culture is manifested through three main forms: (1) the preservation of philosophical customary values through the practice of Piil Pesenggiri, (2) the preservation of regional language and arts in schools and traditional ceremonies, and (3) digitalization and cultural promotion through the utilization of social media and creative content.